2015
DOI: 10.1111/cch.12249
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge mobilization to spread awareness of the ‘F‐words’ in childhood disability: lessons from a family–researcher partnership

Abstract: By creating a short and captivating video, we were able to spread awareness to a wide audience in a short period of time. Engaging families throughout the project was critical to the success of the video. By working together, we hope to continue bridging research and practice and moving the 'F-words' concepts forward one 'word' at a time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 7 publications
0
27
0
2
Order By: Relevance
“…In 2014, an integrated research team, including parents and researchers, formed at CanChild to disseminate and study the uptake of the F‐words proactively. To date, the research team has published two papers on their dissemination work (Cross et al, ; Cross et al, ). The additional four sources in this category described the F‐words research team's work as an example of stakeholder‐driven and knowledge translation research (Longo, Galvão, Ferreira, Lindquist, & Shikako‐Thomas, ; Phoenix et al, ; Rosenbaum, ; Miller & Rosenbaum, ; Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, an integrated research team, including parents and researchers, formed at CanChild to disseminate and study the uptake of the F‐words proactively. To date, the research team has published two papers on their dissemination work (Cross et al, ; Cross et al, ). The additional four sources in this category described the F‐words research team's work as an example of stakeholder‐driven and knowledge translation research (Longo, Galvão, Ferreira, Lindquist, & Shikako‐Thomas, ; Phoenix et al, ; Rosenbaum, ; Miller & Rosenbaum, ; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Since the publication of the F‐words paper in 2012, there has been increasing national and international interest and uptake by people around the world. In 2014, an integrated research team of parents and health services researchers was formed to promote and study systematically the dissemination and implementation of the F‐words in practice (Cross et al, ; Cross, Rosenbaum, Grahovac, Kay, & Gorter, ). Since then, the research team has worked with many stakeholders (including families, service providers, and administrators) to develop and share tools and resources to support the adoption of the F‐words in practice.…”
Section: Introductionmentioning
confidence: 99%
“…This closeness with participants is commonly associated with qualitative research as researchers often invest significant time in building rapport with participants to better understand the depth and context of participant perspectives. Taking the time to interact and establish trust with patients from the start of a study can help to negotiate roles, balance power, and lead to meaningful patient collaboration [ 7 , 17 , 18 ]. Researchers who engage in participatory action research have established methods, histories and successes in joining citizens as equals to design and carry out research to meet the needs as identified by the citizen group in ways that enact change [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…To show how these ideas can be applied, we present an example of the ‘F-words’ integrated knowledge translation research program that began at CanChild in 2014 to disseminate and support the adoption of the ‘F-words’ in Childhood Disability [ 17 , 30 ]. The ‘F-words’ (Function, Family, Fitness, Fun, Friends, and Future) are an operationalization of the World Health Organization’s International Classification of Functioning, Disability and Health (ICF) framework [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The uptake of the F-words among parents and families, and many colleagues around the world, has been gratifying, and variations of these ideas are now widely used (https://www.canchild.ca/en/search?utf8=% E2%9C%93&q=F-words&commit=Search). 2 Many of us are striving to move beyond categorical thinking (avoiding words like normal and abnormal) toward recognition of the individual realities of people, regardless of the extent of their biological or functional differences. Others, however, may still be caught in a time warp of yesterday's thinking.…”
mentioning
confidence: 99%